Investigacion en frijol en Chacras de agricultores del Departamento de Cajamarca, Peru - Cruz R., J.H. de la; Rojas A., E. (International Center for Tropical Agriculture, 1987)
A sample of 342 farmers was surveyed to obtain basic information on bean cultivation in Cajamarca, Peru. A summary of the information is presented including problems detected, cultivation systems, population densities, var., pests, diseases, and input and resource utilization. Expt. were carried out as well as economic, var., and verification essays. Var. Gloriabamba, in combination with the exptl. and farmer technologies, is better than the farmer's var. (CIAT)